2021
DOI: 10.3390/app11041947
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Segmented Correlation Technology in Seismic Communication with Morse Code

Abstract: Seismic communication might promise to revolutionize the theory of seismic waves. However, one of the greatest challenges to its widespread adoption is the difficulty of signal extraction because the seismic waves in the vibration environments, such as seas, streets, city centers and subways, are very complex. Here, we employ segmented correlation technology with Morse code (SCTMC), which extracts the target signal by cutting the collected data into a series of segments and makes these segments cross-correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…We will develop this type of correlation and call it the precise piecewise correlation. It should be emphasized that a segmented correlation, although the term sounds similar to the piecewise correlation, is a type of autocorrelation and a common tool in algorithms that extract a target signal in seismic communication [11].…”
Section: Correlationmentioning
confidence: 99%
“…We will develop this type of correlation and call it the precise piecewise correlation. It should be emphasized that a segmented correlation, although the term sounds similar to the piecewise correlation, is a type of autocorrelation and a common tool in algorithms that extract a target signal in seismic communication [11].…”
Section: Correlationmentioning
confidence: 99%
“…He et al (2017) indicated that a rake receiver can be employed to solve the multipath fading problem of seismic signals using a MATLAB simulation. Jiang et al (2021) compared the characteristics of hammering and vibroseis signals and reported that the vibroseis has an advantage in signal modulation. Jiang et al (2022) proved the feasibility of the aforementioned communication using vibroseis signals and designed two methods for carrier signals.…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al. (2021) compared the characteristics of hammering and vibroseis signals and reported that the vibroseis has an advantage in signal modulation. Jiang et al.…”
Section: Introductionmentioning
confidence: 99%